Kurt Weitzmann e la miniatura carolingia, con una proposta per i busti loricati degli Agrimensori Palatini - Crivello, Fabrizio (Orientalia christiana periodica, 2025)
Kurt Weitzmann pioneered a methodological approach that, integrating archaeological and philological tools, sought to reconstruct lost archetypes of ancient book illustration from their reflections in medieval manuscript decorations. His research encompasses late antique, Byzantine, and Carolingian art, with a notable example being his influential contributions on the ivory panels depicting the Labors of Heracles decorating Saint Peter's throne in the Vatican: he demonstrated that these plaques were produced in the ninth century in the surroundings of the court of Charles the Bald. Weitzmann's studies frequently refer to Carolingian manuscripts copying renowned late antique editions of classical authors, making it possible to reconstruct the decorative program of their models and their possible archetypes. These are the works reflected by the luxury manuscripts from the second quarter of the ninth century collectively referred to as "Einzelhandschriften aus Lotharingien", which later scholarship have placed around the court of Louis the Pious near Aachen. Weitzmann paid particular attention to the armored busts of the Agrimensores Palatini (Vatican City, Biblioteca Apostolica Vaticana, Pal. lat. 1564, f. 1r). A new interpretation of their formal characteristics situates these busts within the milieu of sixteenth-century humanist and antiquarian studies, once more echoing rhetorical models originating from classical scroll illustration.